Cosmética osmótica del balneario de Lanjarón - Carbajo Espejo, José Manuel (Anales de Hidrología Médica, 2008)
We have studied the cutaneous toxicity and the effectiveness of six cosmetic references elaborated with peloids of two springs of the Lanjarón Spa, El Salado (Corporal Moisturizing Lotion) and La Capuchina (Solid Clearing Water, Soft Scrub, Facial Moisturizing Emulsion, Serum and Facial Mask). Harmless was valued by Patch Test and In-use Test in 35 voluntary. Once concluded the In-Use Test, the voluntary ones had to stuff a test of cosmetic indulgence of each one of the references. The results show that globally the cosmetic line is “Good” (Punctuation 7±1,5 on 10) and that it is innocuous under the foreseen use conditions. The containers and the colour and scent of the line were the most controversial aspects and fewer valued, with high standard deviations. So, that if these questions were eliminated the valuation of the contents, it would obtain the punctuation of “Very good” (7,5 ± 0,3). The product more valued was the Facial Mask (“Excellent”: 9,0±1,9) and the one that was valued less the Corporal Moisturizing Lotion (“Good”: 6,6 ±3,1). It is verified in the study that in function of the voluntary panellist’s age, different answers are obtained, being appreciated more the cosmetic for the panellists with more than 30 years, except the Soft Scrub that was more valued by the voluntary ones with less than 30 years.
Keywords: Cosmetic; Peloid; Mud; Mineral water; Salts; Skin; Organoleptic properties